2020
DOI: 10.1186/s12957-020-01815-w
|View full text |Cite
|
Sign up to set email alerts
|

Successful pre-operative local control of skin exposure by sarcoma using combination of systemic chemotherapy and Mohs’ chemosurgery

Abstract: Background: Sarcomas sometimes invade the skin and become exposed, producing malignant wounds characterized by bleeding, exudate, odor, and infection. Malignant cutaneous sarcomas are generally incurable and ultimately impair patients' quality of life. Mohs' chemosurgery is a previously published technique for chemical fixation of a cutaneous tumor and subsequent excision. Case presentation: We present the case of a 44-year-old man with an undifferentiated pleomorphic sarcoma arising in the right chest wall an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…For soft-tissue sarcomas, Mohs paste treatment is used mainly for palliative purposes in superficial ulcerated lesions with bleeding, such as angiosarcomas [ 8 ]. In contrast, Mohs paste treatment can also be used for tumor volume reduction as neoadjuvant therapy for resection in superficial soft-tissue sarcomas [ 9 , 10 , 13 ]. The current method of pre-operative Mohs paste use is a simple and definitive method; the method serves as another treatment option.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For soft-tissue sarcomas, Mohs paste treatment is used mainly for palliative purposes in superficial ulcerated lesions with bleeding, such as angiosarcomas [ 8 ]. In contrast, Mohs paste treatment can also be used for tumor volume reduction as neoadjuvant therapy for resection in superficial soft-tissue sarcomas [ 9 , 10 , 13 ]. The current method of pre-operative Mohs paste use is a simple and definitive method; the method serves as another treatment option.…”
Section: Discussionmentioning
confidence: 99%
“…Mohs paste treatment can be used as neoadjuvant therapy with curative intent. Mohs paste treatment has a role in pre-operative volume reduction in the treatment of pleomorphic sarcomas involving the chest wall [ 9 ]. In the current report, Mohs paste treatment was used to prevent intra-operative bleeding from a subcutaneous sarcoma with a skin ulcer.…”
Section: Introductionmentioning
confidence: 99%
“…It is mainly composed of zinc chloride and was originally developed for curative treatment via repeated fixation and excision until there is complete removal of the tumor ( 6 ). Hoshi et al reported success in the combined treatment using Mohs' paste and neoadjuvant chemotherapy for undifferentiated pleomorphic sarcoma arising in the right chest wall ( 9 ). Systemic chemotherapy and Mohs' paste led to significant shrinkage of the tumor and received wide resection and reconstruction with a rectus abdominis musculocutaneous flap.…”
Section: Discussionmentioning
confidence: 99%
“…Although she had poor general condition at the first presentation to the hospital, RBC transfusion and infusion could improve the hemodynamics. In case of MWs at the first presentation, the microbiological condition is sometimes underrecognized or underestimated because physicians tend to focus on investigating the oncological condition of the patient ( 9 ). However, physicians should consider that MWs can potentially turn into a life-threatening condition when complicated by sepsis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation